THE IMPORTANCE OF GAMIFICATION TO INCREASE STUDENTS' CREATIVITY (Web of Teachers: Inderscience Research, 2025)
This article examines the importance of gamification in enhancing students' creativity in an educational context. By integrating game elements into the learning environment, gamification increases engagement, encourages risk-taking, and fosters collaboration among learners. This framework sets clear goals and rewards, motivating students to seek innovative solutions to problems. In addition, the instant feedback provided through gamified activities allows you to quickly learn from mistakes and develop skills critical to creative thinking. The article highlights how gamification not only transforms traditional educational practices, but also creates a dynamic atmosphere that supports creative research and innovation among students.